2017
DOI: 10.1186/s12889-016-4002-0
|View full text |Cite|
|
Sign up to set email alerts
|

A large and persistent outbreak of typhoid fever caused by consuming contaminated water and street-vended beverages: Kampala, Uganda, January – June 2015

Abstract: BackgroundOn 6 February 2015, Kampala city authorities alerted the Ugandan Ministry of Health of a “strange disease” that killed one person and sickened dozens. We conducted an epidemiologic investigation to identify the nature of the disease, mode of transmission, and risk factors to inform timely and effective control measures.MethodsWe defined a suspected case as onset of fever (≥37.5 °C) for more than 3 days with abdominal pain, headache, negative malaria test or failed anti-malaria treatment, and at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 26 publications
3
66
0
Order By: Relevance
“…A few cases have been reports in Island, India and some areas(May & Senitiri, 2010;Mehndiratta et al, 2012). Besides the disease is rare before the age of 15 years and after 60 years(Kabwama et al, 2017). The patient in the current study is a 10-year-old boy.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…A few cases have been reports in Island, India and some areas(May & Senitiri, 2010;Mehndiratta et al, 2012). Besides the disease is rare before the age of 15 years and after 60 years(Kabwama et al, 2017). The patient in the current study is a 10-year-old boy.…”
mentioning
confidence: 57%
“…Typhoid fever is a systemic disease caused by Salmonella enterica serovar Typhi, a Gram-negative bacterium. Humans are the only host, and transmission most commonly occurs through ingestion of water or food contaminated by feces from an acutely ill or convalescent patient or an asymptomatic carrier (Kabwama et al, 2017). Guillain-Barre' syndrome is a rare complication of typhoid fever (Kapoor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By June, more than 10,000 suspected cases had been reported throughout the five districts in Kampala. The attack rate was higher in males (11.0/1,000 residents) than in females (8.4/1,000 resident) and higher in adults 15 to 59 (12.0/1,000 residents) than in children under 15 (2.0/1,000 residents) (5). The World Health Organization (WHO) reported that contaminated drinking water and juices were the main sources of the outbreak and that most water sources tested were heavily contaminated with Escherichia coli, with groundwater being of the worst quality (see http://www.who.int/csr/don/17-march-2015-uganda/en/).…”
mentioning
confidence: 83%
“…The World Health Organization (WHO) reported that contaminated drinking water and juices were the main sources of the outbreak and that most water sources tested were heavily contaminated with Escherichia coli, with groundwater being of the worst quality (see http://www.who.int/csr/don/17-march-2015-uganda/en/). This was supported by a small-scale study conducted in early April 2015 that detected evidence of fecal contamination in street-vended beverages and in unprotected spring water sources (5).…”
mentioning
confidence: 85%
“…What is very clear is the significant spatial and temporal heterogeneity of typhoid burden in Africa. There has been a well-documented increase in cases throughout East and Central/Southern Africa following multiple introductions of the H58 MDR strain from the Indian subcontinent, and there have been well-described local epidemics and outbreaks with this clade [4,[9][10][11][12] while different non-H58 MDR clades have been shown to circulate in West Africa [13]. The distribution of cases between urban and rural sites is currently unclear and represents a major data gap.…”
Section: Epidemiologymentioning
confidence: 99%